Thermodynamic properties for calcium molybdate, molybdenum tri-oxide and aqueous molybdate ion. (November 2017) - Morishita, Masao; Kinoshita, Yoshiki; Houshiyama, Hiroki; Nozaki, Ai; Yamamoto, Hiroaki
Graphical abstract: Highlights: The present study was done as a part of OECD project contributing nuclear waste management. The thermodynamic properties for CaMoO4, MoO3 and MoO4 2− were investigated. The host crystals of the yellow phases in the nuclear fuel waste glasses. The aqueous ion present in underground water after dissolution of the yellow phases. Abstract: The thermodynamic properties for CaMoO4 (cr), MoO3 (cr) and MoO4 2− (aq) were investigated. CaMoO4 (cr) is the one of the host crystals of the yellow phases which are known as hygroscopic harmful phases in the nuclear fuel glasses. MoO3 (cr) is the main component of the host crystals. MoO4 2− (aq) is the aqueous ion present in underground water after dissolution of the yellow phases. The standard molar entropies, Δ 0 T S m ∘, at 298.15 K for CaMoO4 (cr) and MoO3 (cr) were determined by measuring their isobaric heat capacities, C p, m ∘, from 2 K. Their standard Gibbs energies of formation, Δ f G m ∘, were determined by combining the Δ 0 T S m ∘ data with the reference data of the standard enthalpies of formation, Δ f H m ∘ . The standard electrochemical potential, E °, of MoO4 2− (aq) was determined from the thermodynamic cycle on the basis of thermodynamic properties obtained for CaMoO4 (cr) and MoO3 (cr). The unknown standard Gibbs energies of solution, Δ sln G m ∘, at 298.15 K for the actinide molybdates ThMo2 O8 (cr) and UMoO6 (cr) were predicted from the presently obtained thermodynamic data for CaMoO4 (cr), MoO3 (cr) and MoO4 2− (aq). The obtained thermodynamic values are as follows: Δ 0 T S m ∘ (CaMoO4 (cr), 298.15 K)/(J K −1  mol −1 ) = 122.23 ± 1.22. Δ 0 T S m ∘ (MoO3 (cr), 298.15 K)/(J K −1  mol −1 ) = 75.43 ± 0.75. Δ 0 T S m ∘ (MoO4 2− (aq), 298.15 K)/(J K −1  mol −1 ) = 32.25 ± 4.41. Δ f G m ∘ (CaMoO4 (cr), 298.15 K)/(kJ mol −1 ) = −1437.78 ± 1.11. Δ f G m ∘ (MoO3 (cr), 298.15 K)/(kJ mol −1 ) = −667.20 ± 0.63. Δ f G m ∘ (MoO4 2− (aq), 298.15 K)/(kJ mol −1 ) = −836.61 ± 1.02. E ∘ (MoO4 2− (aq), 298.15 K)/V = 4.34 ± 0.01. Δ sln G m ∘ (ThMo2 O8 (cr), 298.15 K)/(kJ mol −1 ) = 184.84 ± 42.48. Δ sln G m ∘ (UMoO6 (cr), 298.15 K)/(kJ mol −1 ) = 68.33 ± 34.47. The present obtained data are expected to be useful for geo-chemical simulation of diffusion of radio-active elements through underground water.